Analisis pengaruh kualitas pelayanan terhadap kepuasan pasien (studi pada pasien R. S. Condongcatur Yogyakarta) - M. Rizal (Journal of Economics, Business, Accounting and Management, 2023)
Empirical research is needed to determine the effect of direct evidence (tangibles) to the satisfaction of the patient, to determine the effect of reliability (reliability) to the satisfaction of the patient, to determine the effect of the guarantee (assurance) to the satisfaction of the patient, to determine the effect of responsiveness (responsivenes) on patient satisfaction and to determine the effect of empathy (empathy) toward patient satisfaction. The results showed that simultaneous five dimensions of service quality, namely tangibles, reliability, responsiveness, assurance, empathy and a significant positive effect on patient satisfaction in hospital Condongcatur Yogyakarta. The results of this study prove, partially physical evidence significant positive effect on patient satisfaction, reliability significantly positive effect on patient satisfaction, partially guarantee a significant positive effect on patient satisfaction, responsiveness partially significant positive effect on patient satisfaction as well as a empathy partial significant positive effect on patient satisfaction.